Exploring the Contribution of Artificial Intelligence in Combating Plastic Pollution in Oceans - Bhutia, Khandu Doma; Sarkar, Pritam; Kumar, Saurav (Chronicle of Bioresource Management, 2024)
Plastic pollution has emerged as a pressing global environmental concern, posing significant threat to ecosystem, marine life, and human health. Addressing these challenges requires innovative approaches, and the interaction of Artificial Intelligence (AI) as shown promise in tackling various aspect of marine litters. This article explores the concern related to plastic pollution, the impact of marine debris on the marine environment, and potential contribution of AI technologies in combating plastic pollution. The analysis encompasses AI-driven solutions such as image recognition, machine learning algorithms, and AI powered robotics for cleanup operations.